Analysis of carbonate and sulphate attack on concrete structures. (September 2017) - Piasta, Wojciech
Abstract: The current study was designed to explain the progress and causes of damage to structural concrete exposed to atmospheric CO2 and rainwater (23-year old slab) and interactions of atmospheric CO2, rainwater and gypsum (50-year old columns). The testing programme included SEM with EDXA and XRD analysis, and tests determining compressive strength and water absorption. During the carbonation process the basic product identified in the concrete microstructure was calcite or "secondary" calcite, which appeared at the surface of concrete, in the cracks or in the form of dripstone. The formation of ettringite and calcite was observed in the concrete columns exposed to interactions of gypsum, carbon dioxide and rainwater for 50 years. Ultimately, the only product present on the exterior of the concrete was calcite. This is attributed to the conversion of ettringite to calcite due to a direct reaction with CO2 . The test results were compared to the theoretical hypotheses. Highlights: The product of carbonate attack on concrete was calcite, no aragonite was found. No minerals other than calcite occurred in outer precipitations and crack filling. Crack filling and outer dripstones created in process of secondary crystallization. Ettringite and calcite were initially formed due to sulphate and carbonate attack. Final product of simultaneous long-term sulphate and carbonate attack was calcite.